Mechanisms of Epistemic Change—Under Which Circumstances Does Diverging Information Support Epistemic Development? - Kerwer, Martin; Rosman, Tom (Frontiers in Psychology, 2018)
Background. The number of studies on how to foster change towards advanced epistemic beliefs (i.e., beliefs about the nature of knowledge and knowing) is continuously growing because these beliefs are an important predictor of learning outcomes. In past intervention studies, presenting diverging information (e.g., descriptions of studies yielding contradictory results) reliably led to epistemic change. However, prior research insufficiently examined which aspects of diverging information affect these changes. Aims. We investigated (1) if epistemic change differs depending on the (un)resolvability of contradictory information, (2) to what extent explicitly reflecting on diverging information supports epistemic change and (3) how topic-specific diverging information affects topic- and domain-specific epistemic beliefs. All confirmatory hypotheses were preregistered at OSF. Additionally, several exploratory analyses were conducted. Method. To examine the research questions, we employed a simple randomized pre-post design with four experimental groups. N = 185 psychology students participated in the study. Experimental groups differed in the kind of diverging information included: Students either read (1) information on students applying learning strategies (control), (2) unresolvable, or (3a) resolvable controversial information on gender stereotyping. In the latter condition (3b), an additional group of participants deliberately resolved apparent contradictions in a writing task. Results. Confirmatory latent change analyses revealed no significant group differences in epistemic change (i.e., beliefs in the control group also changed towards advanced epistemic beliefs). Using a different methodological approach, subsequent exploratory analyses nevertheless showed that presenting diverging information on gender stereotypes produced stronger topic-specific epistemic change and change in justification beliefs in the treatment groups in contrast to the control group. However, effects in the treatment groups did not differ significantly depending on the resolvability of presented controversies or for the group which was instructed explicitly to integrate controversial findings. Conclusion. Contrary to our expectations, diverging information seems to foster epistemic change towards advanced beliefs regardless of the resolvability of presented information, while no final conclusion concerning effects of reflection could be drawn. Moreover, our findings indicate that effects of topic-specific interventions are more pronounced on topic-specific measures. However, this relationship may vary depending on the epistemic belief dimension (e.g., justification beliefs) under investigation.